“I have adopted it, but i failed”: The critical success factors of lean management implementation among Malaysian public sectors - Zarifa Amira, Zulkeflee; Nawanir, Gusman; Airin, Abdul Ghani (2022)
This paper investigates the critical success factors for the implementation of lean management among the Malaysian public sectors as they are now consistently striving to improve their organizational performance. This cross-sectional quantitative study involved 131 public organisations that were selected through a stratified random sampling procedure. Data were analysed by using the structural equation modelling (SEM) approach with SmartPLS 4.0. Lean resources, lean culture, and lean knowledge management are found to be critical success factors for lean implementation among public sectors in Malaysia, while lean leadership is not. Theoretically, this study is expected to extend the boundaries of knowledge in operations management by looking into public sector organisations from the perspective of the resourcebased view theory. As a result, practitioners and policymakers could gain insights to strategise the implementation of lean management to improve their overall organisational performance